Cartographier les pressions qui s’exercent sur la biodiversité : éléments de réflexion autour des pratiques utilisées - Paul Rouveyrol (Cybergeo)
To better guide conservation policies, it is crucial to understand the mechanisms responsible for biodiversity loss. Maps illustrating anthropogenic pressures on biodiversity represent a rapidly developing technical solution to address this issue. This article, based on a bibliographic review, sheds light on the various stages of their development and questions the relevance of the possible methodological choices. Defining the concepts used to create these maps, particularly the notion of pressure, is a first challenge. Pressure is located precisely at the junction between the different factors of degradation and their consequences. However, the indicators available to us for geographically locating it are generally focused either on the causes or on the consequences of degradation. This pitfall can be overcome if the nature of the indicators used is well defined. To this end, we propose a categorization of pressure indicators, which allows us to link them to the purposes of the map. The cartographic and semiological transformations, including notably the questions of scale and cumulative pressures, are then broken down to highlight the implications of the different possible methodological choices and to draw recommendations. Our results confirm the need to adapt the methods to the use made of the map and argue for better sharing of these methods and their limits.